2015
DOI: 10.1089/ees.2014.0475
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical-Based Design for Treating Ammonia Using Constructed Wetland Systems

Abstract: Constructed wetlands have been used to treat contaminants, including ammonia and nitrate, with varying degrees of success; however, no study has been performed to evaluate ammonia treatment performance of a constructed wetland specifically designed to promote biogeochemical conditions controlling nitrification and denitrification. Therefore, this research aims to improve the design of treating ammonia using constructed wetlands by targeting biogeochemical conditions needed for nitrification and denitrification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…In the studies reviewed, wetland treatment was often used for nitrogen and metals removal in addition to reduction of oxygen demand. Beebe et al (2015) observed both nitrification and denitrification when supplemental aeration and carbon were added in pilot-scale surface and subsurface wetlands treating a simulated produced water (TDS < 1000 mg L −1 ). Pardue et al (2014) observed removal of O&G, iron, and manganese under oxidizing conditions as well as removal of nickel and zinc under reducing conditions; iron removal was variable.…”
Section: Wetlands and Pond Treatmentmentioning
confidence: 96%
See 1 more Smart Citation
“…In the studies reviewed, wetland treatment was often used for nitrogen and metals removal in addition to reduction of oxygen demand. Beebe et al (2015) observed both nitrification and denitrification when supplemental aeration and carbon were added in pilot-scale surface and subsurface wetlands treating a simulated produced water (TDS < 1000 mg L −1 ). Pardue et al (2014) observed removal of O&G, iron, and manganese under oxidizing conditions as well as removal of nickel and zinc under reducing conditions; iron removal was variable.…”
Section: Wetlands and Pond Treatmentmentioning
confidence: 96%
“…Most of the wetland studies reviewed used large containers to construct and simulate wetlands. Beebe et al (2015) used a series of plastic containers (265 L) planted with cattails. Pardue et al (2014) also used a series of plastic containers (378 L each) planted with reeds to simulate subsurface wetlands; free surface wetlands were simulated by planting the containers with bulrush and cattails.…”
Section: Wetlands and Pond Treatmentmentioning
confidence: 99%